Stress shielding prediction of unicortical and bicortical screws: a finite element analysis / Anis Amira Mat Zuki ... [et al.] - Mat Zuki, Anis Amira; Mat, Fauziah; Basaruddin, Khairul Salleh; Daud, Ruslizam; Ahmad, Masniezam; Djamaluddin, Fauzan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The stability in an implant fixation plays a vital role in ensuring proper formation and remodelling process of the fractured bone. Failure in implant fixation is commonly associated with short- and long-term instability of the bone-implant interface. The bone-implant interaction creates a complicated mechanical interplay that might influence the stress distribution and hence the biomechanical performance stability of the implant fixation. Furthermore, implant screw parameters namely thread size, geometrical design and material properties become additional factors that affect the bone-implant interaction. The purpose of this study was to investigate the effect of unicortical and bicortical screws' parameters on the screw-bone interaction mechanism. To evaluate the stress transfers between screw and bone, the stress parameters namely stress transfer parameters (STP) was employed. A two-dimensional (2D) finite element model of full treaded screw was simulated while varying the parameters of the screw: two types of material (stainless steel A316 and titanium alloy Ti-6Al-4V), screw length and screw pitch. It was found that the lower in elastic modulus results to the higher stress transfer between implantbone interface. As the titanium have lower elastic modulus, it gave higher values of STP which help to transmit and distribute stress better compared to the stainless steel. While the effect of varying screw pitch between two types of screws shows that STPs values of fully threaded bicortical screws shows significant result for finer pitch size that may advancing bone remodelling process at the early stage.